THE SPEED CHARACTERISTICS OF THE EARTH'S CRUST OF THE KOROSTEN PLUTON (UKRAINIAN SHIELD) ACCORDING TO THE DATA OF DEEP SEISMIC SOUNDING METHOD - Rozyhan, Y.; Trypilskiy, O.; Topoliuk, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A detailed comparative analysis of the velocity characteristics of the Earth's crust of the Korosten pluton, Volyn and Chopovitsky massifs of the basic rocks of the Volyn megablock of the Ukrainian Shield was carried out. In the interval of depths of 3–13 km in the Earth's crust of the Korosten pluton, five sections are fixed, where the speed on a short interval first decreases with depth, then, on the contrary, increases. This is due to the presence in the section of a series of layers composed of rocks with reduced or elevated speeds, which alternate with increasing depth. Such changes in velocity are considered to be the results of alternation of rocks of the basic and acidic composition. With depth, the rate of increase in velocity (vertical velocity gradient), which characterizes the features of rooting into the crust of an intrusion with increased basicity, significantly decreases. These features lie in the fact that the molten masses coming from the upper mantle were concentrated mainly in the upper and middle parts of the Earth's crust. The distinction between the features of the speed characteristics of the Earth's crust of the Volynsky and Chopovitsky massifs of the main rocks is revealed. The velocity characteristics of the compared structures reflect the characteristics of the rooting of igneous melts of the basic composition into the Earth's crust. Despite the territorial proximity of the massifs, the nature of the rooting of the melts between them is significantly different. For example, abrupt changes in velocity in the depth interval of 0–12 km of the Volynsky massif can be attributed to the presence of, at least, 10 layers of rocks, predominantly of acidic and basic composition, which alternate each other. It should be emphasized that at depths of 8–12 km maximum speeds (up to 0.17–0.18 km/s) between individual layers are observed. In the same depth interval in the Chopovitsky massif, only 5 layers stand out with a maximum differential velocity of 0.18 km/s.
Keywords: Ukrainian Shield; the velocity of seismic waves; vertical velocity gradient; graph V = f (H)